Experimental Stress Analysis on Frame Structure of A 70-Passengers Electric Bus - Stevanus Brian Kristianto; Mohammad Adhitya; Budi Haryanto; Lukyawan Pama Deprian; Umar Abdul Aziz; Ridho Dwimansyah; Danardono Agus Sumarsono (Automotive Experiences, 2025)
Structural strength testing of buses using static vertical load has not previously been explored to validate the structural integrity of bus frames. In this study, the static vertical load method was employed to validate the structural strength of the Universitas of Indonesia electric bus, which utilizes two different materials SS400 for the lower frame and Aluminum Alloy 6061 for the upper frame. Finite Element Analysis (FEA) was conducted to identify critical areas on both the lower and upper frames. The stress values in the simulation were also obtained at the same location as the strain gauge placements in the experiment. Experimental vertical load testing was carried out by incrementally applying a load of 1000 kg up to the equivalent of 70 passengers, with an additional dynamic coefficient of 30% resulting in a maximum load of 6850 kg. Strain measurements were taken using 20 strain gauges on the lower frame and 8 on the upper frame. The experimental result showed the highest stress occurred at strain gauge no. 9 on the lower frame, measuring 78.10 MPa, and 15.32 MPa on the upper frame under 6850 kg load. The comparison between the simulation and experimental results reveals an 18% deviation. Nevertheless, both methods indicate the same critical area of the structure. The stress distribution indicated that the central deck area of the lower frame, where passengers sit and stand, experienced the highest loads. On the upper frame, significant stress was observed in the area where the air conditioning system is mounted. These findings demonstrate that static vertical load testing can be effectively used to validate the structural strength and stress distribution of electric buses, particularly in areas subject to concentrated loading.